High-resolution data shows China's wind and solar energy resources are enough to support a 2050 decarbonized electricity system. (15th January 2022) - Li, Mingquan; Virguez, Edgar; Shan, Rui; Tian, Jialin; Gao, Shuo; Patiño-Echeverri, Dalia
Highlights: Study assesses renewable potential using data with high spatio-temporal resolution. China's wind and solar can provide 1.5 times its 2050 expected electricity demand. There are disparities in renewable development potential across China's regions. Wind and solar energy have different but complementary seasonal patterns. Wind exhibits high seasonal variability while solar exhibits high intra-day variability. Abstract: This study aims to provide a detailed spatial and temporal characterization of China's wind and solar energy resource potential. Quantifying this potential is necessary to identify pathways to achieve a deep decarbonization of its electric power system as this nation pursues carbon neutrality by 2060. This study identifies and characterizes sites suitable for onshore wind and ground-mounted solar PV deployment, quantifies their electricity generation potential, and assesses their spatial heterogeneity across the country and temporal variability throughout the seasons. Resource potential estimates are obtained by combining the latest data with high spatiotemporal resolution with a geographic information system (GIS) analysis that compiles information on wind and solar energy resources, land use, surface elevation and slope, and geomorphology. Results show that China's vast resource potential for wind and solar is enough to provide one-and-a-half times 2050′s expected electricity demand. Results also demonstrate that China's resource-rich areas do not correspond to demand centers, except for provinces like Shandong, Hebei, and Jiangsu, which have high electricity demand and renewable potential. The seasonal patterns show that China should develop wind and solar energy simultaneously, to exploit wind's highest potential during winter and early spring, and solar's higher production during late spring and summer. These findings shed light on the sites that should be prioritized for renewable development and the need to expand power transmission capacity connecting energy-rich areas with load centers, and energy storage capacity and flexible resources to balance variable renewable output with load.